1973
DOI: 10.1002/cpt197314141
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal development of human blood esterases

Abstract: Erythrocyte acetylcholinesterase, plasma proteins, pseudocholinesterase, and arylesterase development was investigated in groups of premature infants of varying gestational ages, comparing the detected levels with those observed in groups of healthy older children and adults. A rapid increase in protein concentration was evident between 28 and 40 weeks gestation, followed by a slower rate of increase until 1 year of age. A rapid increase in plasma pseudocholinesterase and arylesterase activity occurred from 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…In humans, serum PON1 activity is minimal before and at birth, but gradually increases after birth, reaching a plateau between 6 and 15 months of age (Augustinsson and Barr, 1963;Ecobichon and Stephens, 1973;Mueller et al, 1983;Cole et al, 2003). In the present study in mice, Pon1 mRNA expression in mouse liver was very low in the fetus, but rapidly increased at birth, reaching adult levels at 15 days of age (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…In humans, serum PON1 activity is minimal before and at birth, but gradually increases after birth, reaching a plateau between 6 and 15 months of age (Augustinsson and Barr, 1963;Ecobichon and Stephens, 1973;Mueller et al, 1983;Cole et al, 2003). In the present study in mice, Pon1 mRNA expression in mouse liver was very low in the fetus, but rapidly increased at birth, reaching adult levels at 15 days of age (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Studies with chlorpyrifos have indicated that a lower hydrolytic detoxication by PON1 accounts for the differential age-related sensitivity in acute toxicity (Mortensen et al, 1996a;Padilla et al, 2000). The finding of low PON1 activity in neonates (Cole et al, 2003a) suggested that PON1 levels may be even lower before birth, as indeed indicated by data showing a 24% lower activity in premature babies using phenylacetate as a substrate (33-36 weeks of gestation) compared to term babies (Ecobichon and Stephens, 1973). In addition, an expectant mother with low PON1 status would be predicted not to be able to provide protection for her fetus against exposure to some OPs (Cole et al, 2003).…”
Section: Iic5 Paraoxonase (Pon1)mentioning
confidence: 96%
“…Studies in rodents have shown that serum and liver PON1 activity is very low at birth, and increases up to postnatal day 21, with a parallel increase in liver mRNA (Mortensen et al, 1996a;Li et al, 1997;Karanth and Pope, 2000), and similar increases were also seen in transgenic mice expressing either the human PON1 R192 or the PON1 Q192 (Cole et al, 2003c). Studies in humans have also shown that serum PON1 activity is very low at birth and increases over time, reaching a plateau between 6 and 15 months of age (Augustinsson and Barr, 1963;Ecobichon and Stephens, 1973;Mueller et al, 1983;Cole et al, 2003a: Chen et al, 2003. Low PON1 activity during development could represent a relevant risk factor for increased susceptibility to the acute toxicity of certain OP insecticides.…”
Section: Iic5 Paraoxonase (Pon1)mentioning
confidence: 99%
“…However, PON activity at term is approximately half of what it is at age 2 years. 73 Low PON activity relative to HDL cholesterol levels at birth may be part of a nonspecific innate immune system that protects the infant against sepsis as discussed above. However, the persistence of proinflammatory HDL into adulthood may predispose and predict susceptibility to atherosclerosis.…”
Section: Proinflammatory Hdl As a Potential Marker Of Susceptibility mentioning
confidence: 99%